PARACONSISTENT CONTRADICTION IN CONTEXT - Arenhart, Jonas Rafael Becker (Saberes: Revista interdisciplinar de Filosofia e Educação, 2016)
Paraconsistent logics are said to domesticate contradictions: in such logics, expressions such as ? and ¬? do not trivialize the theory. In this sense, we are able to violate the Law of Non-Contradiction. The main problem with this kind of characterization concerns the fact that whenever expressions such as ? and ¬? are both true, they are no longer a contradiction, but at best a subcontrariety. So, perhaps the biggest challenge consists in explaining what is meant by a ‘paraconsistent contradiction’, that is, by a pair of expressions such as ? and ¬? when ‘¬’ is a paraconsistent negation. We suggest that there is a sensible sense in which such expressions may be understood, involving the introduction of distinct contexts from which ? and ¬? are uttered. In this sense, we can read those expressions as formalizing subcontrariety and provide for an intuitive meaning for ‘paraconsistent contradictions’.